Study of monotonic and cyclic mechanical behavior and microstructural evolution at a high temperature of ASTM A297 HP steel modified with niobium. (July 2021) - Vinícius Pereira de Araújo, Marcos; Corrêa de Carvalho, Márcio; Olívio Figueiredo Terra Ruchert, Cassius
Highlights: Determination of mechanical behavior of materials used for oil cracking. Study of niobium alloying on the elastoplastic/viscoelastic behavior. The cyclic stresses with dwell times to precipitation of secondary carbides. Fractography on monotonically fractured specimens and specimens after fatigue. The material is prone to fracture in intergranular regions. Abstract: The present work studies the effects of niobium on the mechanical properties and the elastoplastic/viscoelastic behavior at 927 °C of ASTM A297 grade, HP cast stainless steel in the as-cast material, to simulate the actual work condition. Tensile tests were carried out at different temperatures, differential scanning calorimetry (DSC), relaxation tests, the fatigue of continuous cycles under the triangular waveform, and fatigue with a trapezoidal waveform of the type "Dwell" with dwell times of 120 and 300 s as specified in the E2714-13 standard and hot torsion tests, to analyze the variations in the mechanical properties. The results of the mechanical tests and studies of the microstructural evolution, as well as of its later analyzes, provided data, not only in the form of data sheet's for the application of the values obtained in projects but concurrently after comparing property and microstructure, to deepen the phenomenology of mechanical stress behavior versus monotonic and cyclic deformation, high-temperature deformation mechanisms, dynamic recovery, of the type of microstructure resulting after the tests and also of the fracture mechanisms associated with the types of mechanical stresses imposed on the material, obtained by through the mechanical tests mentioned above. The high-temperature fatigue tests showed expected stress versus strain behavior, where cycles without dwell times showed lower hysteresis area values, from where the energy consumed in a strain cycle is calculated. The increase in the consumed energy values is due to the insertion of the dwell times, but it is important to note that for the tests that contain dwell times of 120 s and 300 s they did not show significant differences between the consumed energy, showing a saturation effect of tension that does not promote more significant inelastic strains. The cyclic mechanical fatigue stresses with dwell times and the low deformation rate led to intense precipitation of secondary carbides Cr23 C6 chromium alloys added to the intrinsic properties of stainless steel dislocation slip were factors that resulted in the dynamic recovery phenomenon. Fractographic analyzes performed on monotonically fractured specimens and specimens after fatigue tests revealed that the material is prone to fracture in intergranular regions.